2005
DOI: 10.1093/jat/29.5.314
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Ketamine Abuse Using Hair Analysis: Concentration Trends in a Singapore Population

Abstract: This paper presents a method for the detection of ketamine in hair. Hair samples (25 mg) were washed, pulverized, and digested in hydrochloric acid (0.5 M) overnight at 45 degrees C. The samples were extracted by an automated solid-phase extraction procedure, and the extracts were subsequently analyzed using gas chromatography-mass spectrometry in selected ion monitoring mode. Linearity up to 120 ng/mg was obtained for both ketamine and norketamine with correlation coefficients of 0.9987 and 0.9985, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 2 publications
3
20
1
Order By: Relevance
“…On the other hand, the ratio of ketamine to norketamine in human hair from ketamine abusers was found to be greater than 1 [16,17]. In the present study, the concentration of norketamine was higher than that of ketamine in the proximal segments of hair from subject #1 (0-1.5 cm), subject #3 (0-3 cm) and subject #4 (0-0.5 cm).…”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…On the other hand, the ratio of ketamine to norketamine in human hair from ketamine abusers was found to be greater than 1 [16,17]. In the present study, the concentration of norketamine was higher than that of ketamine in the proximal segments of hair from subject #1 (0-1.5 cm), subject #3 (0-3 cm) and subject #4 (0-0.5 cm).…”
Section: Discussioncontrasting
confidence: 62%
“…The amount of ketamine present was far below the levels in hair segments from ketamine abusers. Leong et al [17] found that the concentration of ketamine detected in hair from suspected ketamine abusers ranged from 0.6 to 489.0 ng/mg (mean=49.0 ng/mg), whereas the concentration of norketamine ranged from 0.8 [16], the concentration of ketamine detected in hair samples obtained from 15 ketamine abusers was in the range of 0.8 to 92.3 ng/mg (mean=20.5 ng/mg). The mechanisms of drug incorporation into hair have not been established [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also used recreationally as a "club drug" (Degenhardt et al, 2005;Kenyon et al, 2005;Leong et al, 2005), and there is a concern that ketamine may be used to facilitate sexual assault. Methods developed to analyze ketamine and norketamine in various biological matrices are widespread (Bolze and Boulieu, 1998;Yanagihara et al, 2003;Lua and Lin, 2004;Adamowicz and Kala, 2005;Leong et al, 2005;Negrusz et al, 2005;Wang et al, 2005;Apollonio et al, 2006;Xiang et al, 2006) but the analysis of the secondary metabolite dehydronorketamine, and hydroxylated metabolite (both intact and conjugated), is much less common (Adams et al, 1981;Bolze and Boulieu, 1998;Hijazi et al, 2001). At the time of this work, the lack of commercial standards has hindered analysis of these metabolites, whose identification requires custom synthesis (Huang et al, 2005;Wu et al, 2007).…”
mentioning
confidence: 99%
“…Such seldom analysed drugs are g-hydroxy butyric acid (GHB) [115,116], kavain [117], cathinone [118], ketamine [119] as well as a lot of pharmaceutical drugs like benzodiazepines, antidepressants, neuroleptics, antiepileptics, sedatives and hypnotics, anaesthetics, cardiovascular drugs, antibiotics, chemotherapeutics and other drugs as recently summarized in an excellent chapter by Pragst [120].…”
Section: Rare and New Analytes In Hair Analysismentioning
confidence: 99%